The Influence of SARS-CoV-2 Vaccination on the Mortality and Outcomes of Patients with Both Myocardial Infarction and COVID-19 - Eugeniusz Hrycek; Anna Walawska-Hrycek; Krzysztof Milewski; Przemysław Nowakowski; Piotr Buszman; Aleksander Żurakowski (Vaccines)
Background: This multi-site retrospective analysis with a control group was devised to evaluate the impact of prophylactic SARS-CoV-2 vaccination the on outcomes of myocardial infarction (MI) patients with confirmed COVID-19. Methods: An overall of 129 subjects who had been diagnosed with COVID-19 and MI were included in the analysis and were divided into the study group (44 vaccinated patients) and the control group (85 non-vaccinated comparable patients). The primary outcome measure was defined as the time until in-hospital death, while the secondary outcome measure was defined as the time until death outside the hospital setting. Results: According to in-hospital mortality analysis, 1 (2.27%) subject died in the study group, whereas a total of 19 (22.4%) subjects died among the controls (OR = 0.08; CI: 0.001–0.553; p = 0.023). The impact of vaccination on the in-hospital outcomes of patients treated for COVID-19 and MI was further confirmed using Cox regression analysis (HR: 0.1 CI: 0.01–0.77; p = 0.026). The observed difference was the absence of respiratory failure requiring mechanical ventilation in the study group, whereas it was observed in 14 (16.47%) patients in the control group. During out-of-hospital observation, there were no observed differences in mortality (OR: 1.56; 95% CI: 0.21–11.52; p = 0.66). Conclusions: The complete prophylactic SARS-CoV-2 vaccination course demonstrates a protective role in patients undergoing treatment for MI with confirmed COVID-19 during in-hospital observation.